Production of the biomimetic small diameter blood vessels for cardiovascular tissue engineering. Issue 5 (24th March 2019) - Aydogdu, Mehmet Onur; Chou, Joshua; Altun, Esra; Ekren, Nazmi; Cakmak, Selami; Eroglu, Mehmet; Osman, Asila A.; Kutlu, Ozlem; Oner, Ebru Toksoy; Avsar, Gulben; Oktar, Faik Nuzhet; Yilmaz, Ismail; et al.
ABSTRACT: A novel biomimetic vascular graft scaffolds were produced by electrospinning method with the most superior characteristics to be a proper biomimetic small diameter blood vessel using Polycaprolactone(PCL), Ethyl Cellulose(EC) and Collagen Type-1 were used to create the most convenient synergy of a natural and synthetic polymer to achieve similarity to native small diameter blood vessels. Scanning Electron Microscopy(SEM), Fourier Transform Infrared Spectroscopy(FTIR), Differential Scanning Calorimetry Analysis(DSC), tensile measurement tests, and in-vitro and in-vivo applications were performed. Results indicated significant properties such as having 39.33 nm minimum, 104.98 nm average fiber diameter, 3.2 MPa young modulus and 135% relative cell viability. GRAPHICAL ABSTRACT: